A propósito de un caso de eritroleucemia aguda - Bianchi, Andrés E. (1937)
The authors make a study of the bone marrow diseases, refering to an case of this disease, proposing a simple classification of this affections. The authors continue with the description of this classical hematologic form, with the clinical history and with the differential diagnose, considering proved the existence and individuality of this clinical hemathologic form.